Extent of natural soil cadmium, its bioavailability, and pollution treat analysis in the agroforestry systems of the Gedeo Zone of southern Ethiopia - Abdelaali Ait Saghir; Fisseha Asmelash; Melesse Maryo; Ali Boularbah; Fassil Kebede (Heliyon)
The research objectives were to determine extent of soil cadmium (Cd) in the major soil types of the Gedeo Zone of Ethiopia thereby assessing the pollution risk on the environmental health. Four profile pits representing Luvisols, Nitisols, Cambisols, and Leptosols, were excavated and soil samples were collected. Total and available Cd, Cu, Zn, and Mn, including other major soil physicochemical properties, were analyzed in the lab. The permutational multivariate analysis of variance results indicated that the significant (p < 0.05) level of heterogeneity between soil types is confined to subsurface horizons. The nonmetric multidimensional scaling ordination plots also show a marked difference between the physicochemical properties of the subsurface horizons of the Luvisol and the remaining soil types. The mean total Cd levels were high for all soil types and horizons in the range of 5.82–8.48 ppm, however, the mean available Cd contents were low (0.69–0.90 ppm). One-way ANOVA and Kruskal Wallis test results revealed a significant (p < 0.05) soil type effect on total and available Cd contents between the corresponding soil horizons. Based on the single pollution and the Nemerow comprehensive pollution indices, the pollution risk decreases in the order of Cd > Mn > Zn > Cu pollution. According to Pearson's correlation results, no correlation exists between total and available Cd, whereas very strong and significant (p < 0.05) correlations are present between total Cd and total nitrogen (r = 0.90), electrical conductivity (r = 0.83), and organic matter (r = 0.77). Our results indicate that Cd contamination is of geogenic origin, further aggravated by organic matter amendments. More research are needed, among other things, to know the Cd status of the major crops grown in the area so as to design appropriate Cd management strategies.